Uji Kemahiran Berbahasa Indonesia (UKBI) Adaptif Bagi Siswa Kelas XI di SMA MTA Surakarta: Analisis Isi - Abdul Wahid; Kasno Atmo Sukarta; Tadjuddin Nur (CV. Syntax Corporation Indonesia, 2022)
Indonesian Language Proficiency Test is a means to measure a person's proficiency in spoken and written Indonesian. UKBI consists of five sections, namely Section I (Listening), Section II (Responding to Rules), and Section III (Reading) in the form of multiple-choice, as well as Section IV (Writing) in the form of written presentations and Section V (Speaking) in the form of oral presentations. During the current Covid-19 pandemic, UKBI cannot be held offline and in bulk in one place. UKBI Adaptive is a test to measure the language proficiency of Indonesian speakers, which is a new thing for students at SMA MTA Surakarta. Thus it needs to be socialized and tested. This study aimed to determine the mastery of the Indonesian language of class XI students at SMA MTA Surakarta. Descriptive and quantitative methods were used in the research. The results showed that most of the participants scored between 500-700, which means their abilities were in the special and very superior categories. Thus, it can be said that UKBI is a test tool that can be used to measure the mastery of the Indonesian language and the use of good and correct Indonesian by students